Leaves to Measure Light Intensity - Lahlou, Aliénor; Coghill, Ian; Davidson, Mhairi L H; Billon, Romain; Barneche, Fredy; Lazar, Dusan; Le Saux, Thomas; Jullien, Ludovic (Advanced science (Weinheim, Baden-Wurttemberg, Germany), 2024)
Quantitative measurement of light intensity is a key step in ensuring the reliability and the reproducibility of scientific results in many fields of physics, biology, and chemistry. The protocols presented so far use various photoactive properties of manufactured materials. Here, leaves are introduced as an easily accessible green material to calibrate light intensity. The measurement protocol consists in monitoring the chlorophyll fluorescence of a leaf while it is exposed to a jump of constant light. The inverse of the characteristic time of the initial chlorophyll fluorescence rise is shown to be proportional to the light intensity received by the leaf over a wide range of wavelengths and intensities. Moreover, the proportionality factor is stable across a wide collection of plant species, which makes the measurement protocol accessible to users without prior calibration. This favorable feature is finally harnessed to calibrate a source of white light from exploiting simple leaves collected from a garden.
Keywords: fluorescence; irradiance; green materials; actinometry; photoactive materials; light intensity